2013
DOI: 10.1371/journal.pone.0064510
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone Is Not Associated with Cardiometabolic Risk Factors in Adolescent Females

Abstract: ObjectivesEpidemiological evidence for associations of Anti-Müllerian hormone (AMH) with cardiometabolic risk factors is lacking. Existing evidence comes from small studies in select adult populations, and findings are conflicting. We aimed to assess whether AMH is associated with cardiometabolic risk factors in a general population of adolescent females.MethodsAMH, fasting insulin, glucose, HDLc, LDLc, triglycerides and C-reactive protein (CRP) were measured at a mean age 15.5 years in 1,308 female participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Of 11 studies that reported results from healthy women on the association of BMI with AMH concentrations (9, 27, 28, 3133, 36, 4144), seven reported no significant association (9, 27, 36, 4144), whereas four observed a significant inverse association (28, 3133). Our non-significant association between BMI and AMH is consistent with the results from most studies of healthy women.…”
Section: Discussionmentioning
confidence: 99%
“…Of 11 studies that reported results from healthy women on the association of BMI with AMH concentrations (9, 27, 28, 3133, 36, 4144), seven reported no significant association (9, 27, 36, 4144), whereas four observed a significant inverse association (28, 3133). Our non-significant association between BMI and AMH is consistent with the results from most studies of healthy women.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no correction for confounders besides age and BMI, such as smoking status [29]. In cross-sectional research conducted in a large cohort of adolescent females, AMH quintile was not associated with lipid and blood glucose levels and insulin resistance, nor with C-reactive protein (CRP) levels [30]. This was supported by another study among adolescents [31], including subjects with a diagnosis of PCOS (5.3%).…”
Section: Relationship Of Amh With Metabolic Parametersmentioning
confidence: 96%
“…Maternal adiposity has previously been shown to decrease the probability of pregnancy in women undergoing IVF with autologous oocytes but not donor oocytes, suggesting that this effect is mediated via oocyte quality not endometrial receptivity (32,33). Consistent with this, obesity as determined by both BMI and dual energy X-ray absorptiometry determined that fat mass has been shown to not influence maternal AMH measurements, suggesting that the negative effect is not mediated through oocyte quantity (34,35).…”
Section: Tablementioning
confidence: 66%